Urban Interiority and the Spatial Processes of Securitisation in Medellin: A Speculation on the Architectures of Reassurance - Deluchi, Christina (Interiority, 2018)
Medellín, Colombia, a city best known for its violent history and subsequent radical transformation, hosts multiple political forces of varying degrees of legitimacy. In this context, architecture was mobilised as a physical weapon in the city’s urban regions. As an extension of this architectural condition, the city’s landscape has repeatedly been appropriated and repurposed to enforce state and criminal agency. Medellín’s cultural geography became increasingly unstable as both real and imagined threats lingered in the spaces of every day – apartment towers, gated communities, supermarkets, TV and radio, imbued with violent operational spatial logics. In detecting processes of regulation, protection, and surveillance, the political instrumentality and larger urban implications of interior space in Medellín are revealed through architectural objects and spatial devices of control. As techniques of securitisation, these processes provide evidence for the construction of Medellín’s interiority, an urban condition founded on political violence and withdrawal. The objects and devices of this interiority are often remarkably ordinary, yet they are the political tools that indoctrinate a military-style urbanism that interprets, registers, and shapes territorial conflict. The mobilisation of Medellín’s interiority in the pursuit of power and control has manufactured an urban imaginary governed by the constant threat of violence.